Design of Controller for Submersible Water Pump Based on Solar Energy - Mankar, Tejashwaree D.; Krirsagar, Ravi. V. (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
This project work deals with the development of low cost PV pumping system using a PMBLDC (permanent magnet brushless dc motor) drive coupled to a pump load. We are proposing to design and develop a constant current controller without current and position sensors therefore reducing to a large extent the overall cost of the drive system and to maintain the required output in case of low solar insolation during the winter and also in case of reduced solar output due to increase in cell temperature. The controller will drive a PMBLDC motor to pump the water to the tank. The input from the water level sensors attached to the tank indicates the water level to the controller and thereby automates the pumping system.